Categorizing facial creases: A review - Hadi, Helmi; M. Wilkinson, Caroline (Wiley, 2016)
Ensuring uniformity in the nomenclature standardization of facial creases is important to enable the scholarly community to follow and debate the advancements in research. This review highlights the prevailing disparity in the nomenclature that refers to the same facial crease by researchers and laypeople, and suggests uniform names for the facial creases based on available literature. The previous and current trends in facial crease classification are also discussed. The nomenclature of the facial creases considered for this review include the following: the nasolabial fold, corner of the mouth lines, upper and lower lip creases around the mouth region, the mandibular folds, the bifid nose, the transverse nasal line, the vertical glabellar line, chin crease, the mental crease, four type of creases around the eyes, forehead creases, and periauricular creases. A figure illustrating the above facial creases is included as reference. It is hoped that the proposed standardization of nomenclature would ensure a more scientific referencing of facial creases enabling more effective scientific interaction among the scholarly community as well as the laypeople interested in the research and application of facial creases.